FRAMING NEGATIVE ATTITUDES TOWARD PROPHET MUHAMMAD AND ISLAM IN THE ORIENTALIST THOUGHT OF ROBERT SPENCER - Hidayat, Rahmat (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
Islam, as a major world religion, continues to face various challenges in the context of Western intellectual discourse, particularly from orientalists. One of the most prominent figures in this regard is Robert Spencer, an anti-Islamic scholar known for his controversial work The Truth About Muhammad: Founder of the World’s Most Intolerant Religion, which has generated significant debate and been banned in certain countries. This paper aims to critically analyze Spencer's portrayal of the Prophet Muhammad and Islam, focusing on the framing techniques he employs to present a biased and distorted narrative. The study explores how Spencer's selective interpretation of Islamic texts and historical events constructs a negative image of the Prophet Muhammad, which aligns with broader Orientalist discourse. Additionally, this paper examines Spencer's role as an activist within the Counter Jihad movement and his influence on shaping Western public perceptions of Islam. The findings underscore the ideological motivations behind his work and the implications for interfaith understanding and global perceptions of Islam.